2018
DOI: 10.1016/j.dib.2018.08.130
|View full text |Cite
|
Sign up to set email alerts
|

Simulation basis for a techno-economic evaluation of chitin nanomaterials production process using Aspen Plus® software

Abstract: Process simulation is a useful tool that has been widely used to analyze, design and optimize energy balances in chemical technologies including those related to biomass processing, biorefinery processes and chemical engineering. The presented data set serves as basis for the simulation of chitin purification, nanofibers and nanocrystals production processes, considering laboratory experimental procedures described in previous experimental articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Several simulation tools or software are available, and the main ones are Aspen Plus, Aspen HYSYS, ChemCAD, Unisim Desing, SuperPro Designer, among others, which have been used successfully by different authors. For example, Oregigioni et al simulated the production of biomethane production from agricultural and food industry waste, and Larbi et al simulated the production of chitin nanomaterials; both emerging processes were simulated to analyze economic feasibility. On the other hand, Mestre-Escudero et al simulated existing processes such as the amine treatment unit, mercaptan oxidation unit, and sour water unit of a Latin American refinery to determine improvement opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Several simulation tools or software are available, and the main ones are Aspen Plus, Aspen HYSYS, ChemCAD, Unisim Desing, SuperPro Designer, among others, which have been used successfully by different authors. For example, Oregigioni et al simulated the production of biomethane production from agricultural and food industry waste, and Larbi et al simulated the production of chitin nanomaterials; both emerging processes were simulated to analyze economic feasibility. On the other hand, Mestre-Escudero et al simulated existing processes such as the amine treatment unit, mercaptan oxidation unit, and sour water unit of a Latin American refinery to determine improvement opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Granjo et al [29] made use of Aspen Plus and Monte Carlo simulation to evaluate different manufacturing methods of sodium methoxide. More recent works on technoeconomic analysis based on Aspen Plus simulation have been reported for supercritical CO 2 extraction of Eucalyptus globulus bark [30], chitin nanomaterials production [31], and anaerobic digestion of sugarcane vinasses for biogas production [32]. Moreover, there were authors who reported the use of SuperPro Designer for technoeconomic analysis of various biochemical, pharmaceutical, and food processes.…”
Section: Introductionmentioning
confidence: 99%
“…Aspen Plus software process simulation is used in computeraided design, process optimization (e.g., improving production and process efficiency, minimizing operational costs and emission of waste that may be contaminant, improving energy efficiency, etc. ), solving operational problems, and so on [18][19][20]. In this paper, optimization of the process for the separation of NaCN and Na 2 CO 3 mixtures in a water-ethanol mixed solvent was carried out.…”
Section: Introductionmentioning
confidence: 99%